2021
DOI: 10.3390/medicina57020160
|View full text |Cite
|
Sign up to set email alerts
|

Serological Parameters and Vascular Investigation for a Better Assessment in DVT during Pregnancy—A Systematic Review

Abstract: Pregnancy and the postpartum period represent a condition characterized by a thrombotic predisposition. The majority of pregnant women do not face acute or severe thrombotic events. In general, mild inconveniences such as leg swelling or moderately painful thrombotic events (phlebitis) are encountered. However, when pregnancy is associated with inherited or acquired deficits that affect homeostasis, the risk of acute or even life-threatening events can increase significantly. The major consequence is the loss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…[ 25 ] Almost all coagulation factors increas to varying degrees during the middle of the pregnancy, and peak at the time of delivery. [ 26 ] Post-operatively, patients are usually advised bed-rest for 24 hours. The reduced activity of the lower limbs as well as reduced mobility leads to slowing and stasis of the blood flow, predisposing these patients to the development of deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 25 ] Almost all coagulation factors increas to varying degrees during the middle of the pregnancy, and peak at the time of delivery. [ 26 ] Post-operatively, patients are usually advised bed-rest for 24 hours. The reduced activity of the lower limbs as well as reduced mobility leads to slowing and stasis of the blood flow, predisposing these patients to the development of deep vein thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Differential diagnosis is an important step in the prenatal and postnatal evaluation of fetal ovarian cysts, as many other abdominal or pelvic masses can mimic this pathology [19,20], and serological markers could be helpful in the postnatal differentiation of various types of masses [21,22]. Thus, we included only cases with highly suggestive ultrasound appearances of FOC in our study.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a large number of studies indicate that Hcy is an independent risk factor for cardiovascular disease and that there is a higher correlation between homocysteine and atherosclerosis levels than between cholesterol and atherosclerosis levels [ 78 , 83 ]. Hcy is thought to be associated with vascular dysfunction through the following mechanisms: generation of reactive species (ROS), triggering/maintaining the inflammatory response; initiation of thrombotic phenomena [ 80 , 84 ]. Endothelial dysfunction is one of the major events in the pathogenic mechanism of cardiovascular disease.…”
Section: Inherited Thrombophiliamentioning
confidence: 99%
“…The literature indicates a link between homocysteine and reactive species. Hcy is a risk factor for thrombophilia and is associated with both venous thrombosis and arterial thrombosis [ 84 ]. A study by Ridker et al, over a period of 10 years, showed that the combination of hyperhomocysteinemia and Leiden factor V further increases the risk of venous thromboembolism [ 88 ].…”
Section: Inherited Thrombophiliamentioning
confidence: 99%